On the existence and enumeration of sets of two or three mutually orthogonal Latin squares with application to sports tournament scheduling - Kidd, Martin Philip (Stellenbosch : Stellenbosch University, 2012)
Thesis (PdD)--Stellenbosch University, 2012.